National Vocational Aptitude Tests for Primary Schools Including General Knowledge Book 3 - Ugo, Ugo C (Ugo c Ugo Publishing Company Limited, 1997)
This book is a series of six books designed to assist children in the primary schools for the development of their various mental,social and Psychological skills.
Keywords: Education- General Knowledge